Parenting in the Perspective of Al-Ghazali - Wardhatus Sa’adah; Andini Afiatus Sholehah (Al-Hikmah: International Journal of Islamic Studies, 2025)
Parenting style is a pivotal factor influencing a child’s character, social skills, and emotional development. In contemporary psychological and educational studies, parenting styles are commonly categorized into permissive, democratic, and authoritarian, each exerting distinct impacts on children’s behavior and developmental outcomes. Democratic parenting, characterized by balanced authority and open communication, has been shown to foster independence, social competence, and emotional resilience in children. Conversely, authoritarian parenting often correlates with lower social adaptability and heightened aggressive tendencies. Moreover, early integration of moral and spiritual education significantly contributes to the holistic formation of a child’s character, aligning with perspectives that emphasize the centrality of religious values in parenting. In this regard, Al-Ghazali’s thought offers a profound framework, highlighting the necessity of instilling moral virtues and spiritual discipline from an early age as an integral part of nurturing a righteous and well-balanced individual. This study underscores the intersection of modern parenting theories with classical Islamic thought, providing a comprehensive understanding of how parenting styles, when infused with moral-spiritual guidance, can shape children’s character in a transformative and sustainable manner